Quality by Design-Driven HPLC Method Development for Quantification of Resveratrol in Bulk and Pharmaceutical Dosage Form and its Validation - Raysing, Swati Devendra; Gorle, Ashish Prakash (Indian Journal of Pharmaceutical Education and Research, 2025)
Background The purpose of the recent research was to establish a simple, efficient, sensitive and accurate High-Performance Liquid Chromatography (HPLC) method for estimating Resveratrol (RVT) in bulk and pharmaceutical dosage form based on Quality by Design (QbD). As risk assessment and statistics are not used in a conventional approach, the Analytical Quality by Design (AQbD) was employed with scientific techniques including Analytical Target Profile (ATP), Critical Quality Attributes (CQA), Design of Experiment (DoE), method validation and continuous method monitoring for RVT quantification. Materials and Methods To execute this work, a Central Composite Design (CCD) was employed to make the method robust and effective in developing a chromatographic database. Using a fractional factorial design, the factors were screened. Results The optimized chromatographic conditions were achieved using a C18 (250x4.6 mm, 2.5m) column at 25ºC with methanol and 0.05% Ortho-Phthalaldehyde (OPA) buffer pH 2.8 in a 50:50, v/v ratio as the mobile phase and a flow rate of 0.7 mL/min, at 319 nm of detection wavelength. The RVT's retention time was observed to be 3.64 min. The precision and accuracy results were within the specified limits (<2% RSD). Conclusion The proposed QbD-based method proved to be helpful for critical analysis is RVT in the bulk and pharmaceutical dosage forms. Hence, it can be employed for routine analysis in quality control laboratories.
Keywords: Resveratrol; High-Performance Liquid Chromatography; Central Composite Design; Quality by Design; Validation.